PENERAPAN METODE LATIHAN UNTUK MENINGKATKAN KEMAMPUAN GURU BAHASA INDONESIA MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR DI SDN 003 ROKAN IV KOTO - Yanis, M. (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
From the observations, this time the teachers are still very rarely utilize the schoolenvironment as a learning resource. The school environment is not only used as a place tofrolic students during recess. Otherwise recess, teachers often choose quarantining studentsin the classroom, although the example of students have felt very saturated in the classroom.This research is a school action. Subjects in this study were as many as 17 teachers. Based onthe analysis and discussion of the first cycle and the second cycle, it can be concluded that theability of Indonesian teachers in the use of the school environment as a learning resourcethrough increased training approach. This is evidenced, in the first cycle ability of teacherswho earn enough categories numbered 11 persons (64.7%). And that gets the category of lessnumbered 6 (35.3%). In the second cycle that gets both categories amounted to 14 (82.4%).While categorized quite totaling 3 (17.6%).